Volume 8: Seismic Engineering 2011
DOI: 10.1115/pvp2011-57726
|View full text |Cite
|
Sign up to set email alerts
|

The Parameter Study of the Seismically Isolated Bridge System by Lead Rubber Bearing Based on Energy Analysis

Abstract: The energy response equations of the seismically isolated bridge system are established based On the energy equilibrium theory. Bilinear analysis model of the energy response of the seismically isolated bridge is constructed by series connecting the bridge piers and the Lead rubber bearings. According to the applicable Code of Seismic Design for Railway Engineering, forty strong ground motion records are appropriately selected as the seismic input and the nonlinear time history analyses for the seismic energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…e right-hand side is the seismic input energy E O (t). Equation ( 7) can be written into equation (8), and the kinetic energy of the system and the elastic strain energy are given in equations ( 9) and ( 10):…”
Section: Energy Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…e right-hand side is the seismic input energy E O (t). Equation ( 7) can be written into equation (8), and the kinetic energy of the system and the elastic strain energy are given in equations ( 9) and ( 10):…”
Section: Energy Equationsmentioning
confidence: 99%
“…Ismail et al [6,7] carried out numerical simulation of the seismic performance of cable-stayed bridges using a Roll-N-Cage (RNC) isolator and showed that the RNC isolator is a convenient isolation system in protecting cable-stayed bridges against near-fault (NF) earthquakes. Zhong et al [8] studied the influences of the peak ground accelerations, the principal dynamic parameters on the input energy, and the hysteretic energy ratio using lead rubber bearing as isolation devices. Different isolation designs were studied by Dicleli et al [9], Taflanidis [10], and Ates and Constantinou [11] for their effectiveness against seismic waves, including the probabilistic performance, and for applications to different bridge designs, such as for curved bridges and cable-stayed bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic isolated bearing installed in bridge can escape or mitigate the bridge damage and provides the effective protection for bridge during earthquake. Therefore, the researchers from many countries have carried out a lot of important research work on seismic isolation technology in the past twenty years [1][2][3][4]. At the same time, good anti-seismic performance has been verified in some earthquakes.…”
Section: Introductionmentioning
confidence: 99%